2022
DOI: 10.1017/s104161022100274x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative delirium and its relationship with biomarkers for dementia: a meta-analysis

Abstract: Objectives This study seeks to identify Alzheimer’s and related dementias (ADRD) biomarkers associated with postoperative delirium (POD) via meta-analysis. Design: A comprehensive search was conducted. Studies met the following inclusion criteria: >18 years of age, identified POD with standardized assessment, and biomarker measured in the AT(N)-X (A = amyloid, T = tau, (N)=neurodegeneration, X-Other) framework. Exclusion criteria: focus on prediction of delirium, delirium superimposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…S-100β has been found to be significantly elevated in the serum of patients who have experienced or are experiencing delirium ( Khan et al, 2021 ), suggesting that there might be a close relationship between delirium and nerve injury and that factors such as surgery, hemorrhage, anesthetic drugs, and perioperative hypoperfusion might cause cerebral injury and contribute to the development of delirium. It has been reported that S-100β in the blood is positively correlated with the occurrence of POD ( Wang et al, 2022 ). Axons release small amounts of NfL—an important component subunit of neuronal neurofilament proteins—under normal physiological conditions, but under pathological conditions, the synthesis and release of NfL increases significantly.…”
Section: Discussionmentioning
confidence: 99%
“…S-100β has been found to be significantly elevated in the serum of patients who have experienced or are experiencing delirium ( Khan et al, 2021 ), suggesting that there might be a close relationship between delirium and nerve injury and that factors such as surgery, hemorrhage, anesthetic drugs, and perioperative hypoperfusion might cause cerebral injury and contribute to the development of delirium. It has been reported that S-100β in the blood is positively correlated with the occurrence of POD ( Wang et al, 2022 ). Axons release small amounts of NfL—an important component subunit of neuronal neurofilament proteins—under normal physiological conditions, but under pathological conditions, the synthesis and release of NfL increases significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have conducted a number of clinical studies to identify biomarkers accurately predicting PODs, such as the evaluation of plasma tau, 31 the S‐100β protein, 32 amyloid, 33 adiponectin 34 levels, and the level of PGRN in the cerebrospinal fluid. 35 Researchers are also trying to determine how to reduce the prevalence of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, this study showed that postoperative CRP level was a good predictor for POD in CRC patients, which was in consistent with the results by previous meta-analyses. 15,17 Age was a well-established risk factor for delirium, and was an independent predictor for delirium. [46][47][48][49] As expected, we found that older age (> 70 years) was a risk factor for POD in patients with CRC by multivariate analysis, which was not shown in the study by Xiang et al 36 They showed that the age was a risk factor for POD in univariate analysis, but not in multivariate analysis, 36 , which might be due to limited sample size or clinical heterogeneity.…”
mentioning
confidence: 99%